Impact of date palm fruits extracts and probiotic enriched diet on antioxidant status, innate immune response and immune-related gene expression of European seabass (Dicentrarchus labrax). (May 2016) - Guardiola, F.A.; Porcino, C.; Cerezuela, R.; Cuesta, A.; Faggio, C.; Esteban, M.A.
Abstract: The application of additives in the diet as plants or extracts of plants as natural and innocuous compounds has potential in aquaculture as an alternative to antibiotics and immunoprophylactics. The aim of the current study was to evaluate the potential effects of dietary supplementation of date palm fruit extracts alone or in combination with Pdp11 probiotic on serum antioxidant status, on the humoral and cellular innate immune status, as well as, on the expression levels of some immune-related genes in head-kidney and gut of European sea bass ( Dicentrarchus labrax ) after 2 and 4 weeks of administration. This study showed for the first time in European sea bass an immunostimulation in several of the parameters evaluated in fish fed with date palm fruits extracts enriched diet or fed with this substance in combination with Pdp 11 probiotic, mainly after 4 weeks of treatment. In the same way, dietary supplementation of mixture diet has positive effects on the expression levels of immune-related genes, chiefly in head-kidney of Dicentrarchus labrax . Therefore, the combination of both could be considered of great interest as potential additives for farmed fish. Highlights: Effects of dietary date palm fruit extracts alone or in combination with Pdp11 probiotic were tested. Date palm fruit extracts have immunostimulant properties for European sea bass. Mixture diet has many positive effects on the immune-related gene expression. The combination of immunostimulant and probiotics in fish diet is discussed.